A balanced scorecard approach for strategy- and quality-driven universities - Cardoso, E.; Trigueiros, M. J.; Narciso, P. (11th International Conference of European University Information Systems (EUNIS 2005), 2005)
This paper describes a Balanced Scorecard Strategic System integrated in the Decision Support Systems for University Effectiveness and Efficiency (DSS-UEE) project, developed at the Department of Sciences and Information Technologies (DCTI) of Instituto Superior de Ciências do Trabalho e da Empresa (ISCTE), a Management, Social Sciences and Informatics University in Lisbon. This Strategic System is presented as the main system driving the departmental level implementation of an effective Information Architecture at ISCTE.